A draft genome sequence of the elusive giant squid, Architeuthis dux. Issue 1 (16th January 2020) - da Fonseca, Rute R; Couto, Alvarina; Machado, Andre M; Brejova, Brona; Albertin, Carolin B; Silva, Filipe; Gardner, Paul; Baril, Tobias; Hayward, Alex; Campos, Alexandre; Ribeiro, Ângela M; Barrio-Hernandez, Inigo; et al.
ABSTRACT: Background: The giant squid ( Architeuthis dux ; Steenstrup, 1857) is an enigmatic giant mollusc with a circumglobal distribution in the deep ocean, except in the high Arctic and Antarctic waters. The elusiveness of the species makes it difficult to study. Thus, having a genome assembled for this deep-sea–dwelling species will allow several pending evolutionary questions to be unlocked. Findings: We present a draft genome assembly that includes 200 Gb of Illumina reads, 4 Gb of Moleculo synthetic long reads, and 108 Gb of Chicago libraries, with a final size matching the estimated genome size of 2.7 Gb, and a scaffold N50 of 4.8 Mb. We also present an alternative assembly including 27 Gb raw reads generated using the Pacific Biosciences platform. In addition, we sequenced the proteome of the same individual and RNA from 3 different tissue types from 3 other species of squid ( Onychoteuthis banksii, Dosidicus gigas, and Sthenoteuthis oualaniensis ) to assist genome annotation. We annotated 33, 406 protein-coding genes supported by evidence, and the genome completeness estimated by BUSCO reached 92%. Repetitive regions cover 49.17% of the genome. Conclusions: This annotated draft genome of A. dux provides a critical resource to investigate the unique traits of this species, including its gigantism and key adaptations to deep-sea environments.